Impact of Peace Values on the Religious Behavior of Young Citizens at Public Religious Universities - Apandie, Chris; Rahmelia, Silvia (Indonesian Center for Religion and Society Studies (InTReSt), 2024)
Religious conflicts still occur in the social life of pluralistic Indonesian society, one of the causes is the absence of peace values that are manifested in the religious behavior of citizens. Researchers have the assumption that the values of peace understood by students as young citizens can affect the religious behavior displayed. Therefore, this study aims to find how much influence the perception of peace values has on the religious behavior of young citizens at State Religious Universities in Central Kalimantan. This research uses a quantitative approach with a correlational research type. The research was conducted at 3 (three) State Religious Universities in Central Kalimantan Province with 183 respondents as samples, namely students as young citizens with an age range of 18-24 years. This study uses data collection techniques in the form of a questionnaire using a Likert scale. Validity and reliability test used the help of the SPSS application with the normality test stage using the Kolmogorov Smirnov test, the linearity test with a significance value criterion of 0.05 and the hypothesis testing stage using the simple linear regression equation formula. Results of the data analysis of this study indicate that peace values affect the religious behavior of young citizens in State Religious Universities in Central Kalimantan Province by 65%. The existence of a strong correlation between peace values and religious behavior provides an important recommendation for government policy as well as supporting UN 2030 Agenda. Improving peace building in this case can be taught in the implementation of peace education with peace values consisting of making peace with God, self, others, the environment and other incidental themes.